ANALISIS MOTIVASI DAN HASIL BELAJAR SISWA DI MASA PANDEMI COVID-19 MELALUI PEMBELAJARAN DARING PADA MATA PELAJARAN PPKn KELAS VII F SMP NEGERI 3 WATAMPONE - Rusdi, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research is descriptive qualitative by using qualitative analysis design. In this study, what was analyzed were the motivation and learning outcomes of Class VII F Civics during the COVID-19 Pandemic through Online Learning. In the process of collecting research data using observation techniques, interviews, documentation. and using data analysis techniques, namely data reduction, data display/data presentation, and conclusion drawing. Based on the discussion and results of data analysis, it can be concluded that Student Motivation and Learning Outcomes During the COVID-19 Pandemic through Online Learning in Civics Subjects in Class VII F of SMP Negeri 3 Watampone can increase. This is evidenced by the increase in motivation and learning outcomes, where students' learning motivation is predicated A- with a score of 87.00 and learning outcomes with an A- predicate with a value of 86.10.